Stress urinary incontinence: injection method of treatment (literature review) - E I Ermakova (IP Berlin A.V., 2018)
The purpose of the review - presentation of clinical scientific data based on current evidence of information on the management of patients with stress urinary incontinence, the effectiveness and safety of periurethral injections of various bulking substances. Material and methods. А review of Russian and foreign sources on the prevalence, etiopathogenesis, diagnosis and treatment of stress urinary incontinence in women, in particular the injection method. Results. The review presents data of the etiopathogenesis, diagnosis and treatment of stress urinary incontinence in women, depending on the severity of the pathology. Analyzed the data of periurethral injection of various bulking materials, their effectiveness and safety.